2023
DOI: 10.1186/s12879-023-08893-7
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline vs azithromycin in patients with scrub typhus: a systematic review of literature and meta-analysis

Nitin Gupta,
Carl Boodman,
Christelle Genevieve Jouego
et al.

Abstract: Introduction Scrub typhus is a bacterial mite-borne disease associated with poor clinical outcomes if not treated adequately. The study aimed to compare the time to defervescence, clinical failure, mortality and treatment-related adverse effects of two common drugs (doxycycline and azithromycin) used for its treatment. Methodology This was a systematic review and meta-analysis. All studies up to 20.03.2023 were screened for eligibility in Pubmed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…One study reported their results using median and range [ 30 ]. To estimate the means and standard deviations of this study, a previously described formula was used [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…One study reported their results using median and range [ 30 ]. To estimate the means and standard deviations of this study, a previously described formula was used [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%